Pengaruh Lokasi, Harga dan Promosi Terhadap Keputusan Pembelian Getuk Pisang Bariklana Tulungagung - Octavinany, Bella Regina; Umami, Nailariza (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research investigates the influence of location, price, and promotion on consumer purchase decisions for Getuk Pisang Bariklana products in Tulungagung. This decline is assumed to stem from a combination of external factors, including a potentially less strategic business location, a relatively higher price compared to similar competing products, and promotional activities deemed insufficiently broad and effective in reaching the target market. To achieve the research objectives, a quantitative approach was employed using a survey method. Data was collected by distributing questionnaires to 100 respondents, who are consumers of Getuk Pisang Bariklana in Tulungagung. The data analysis technique applied was multiple linear regression. This method was chosen to comprehensively examine and measure the extent to which each independent variable (partially and simultaneously influences consumer purchase decisions.The research results indicate that, partially, the location, price, and promotion variables significantly influence purchase decisions, each with a significance value of p < 0.05. Simultaneously, these three variables also significantly influence purchase decisions, evidenced by an F significance value of 0.000. The coefficient of determination of 0.510 indicates that 51% of the variation in purchase decisions can be explained by the location, price, and promotion variables, while 49% is explained by other factors outside this research model.